Multidisciplinary Care and Physician Workload: Pathways to Safer, More Patient-Centered Medicine - FELIMBAN, HAZIM HUSSAIN; ALLOQMANI, SALEH MANEEA; KHAN, DR.WESSAM KHALID; KHAN, KARRAM KHALID; BAJAHLAN, SALEH OMAR; AL-GRAIGRI, DR.BARAA HAMAD; TELMISANI, NORAH ABDULRAHMAN; EDREES, MAHER AHMED; ALSULAMI, IBRAHIM ABDULALIM HOMAIDAN; ALZAHRANI, AMAL BAKHEET; BUKHARI, ORJUWAN FUAD; MOHAMMED, ESSAM ABDULLAH; et al. (Journal of Posthumanism, 2024)
The reason for multidisciplinary care is to deal with the fact that illness is caused by many things. Chronic diseases like diabetes, cancer, and heart failure need help from many different areas of medicine. In real life, this often means having regular meetings with the whole team, making treatment plans that everyone can see, and sharing paperwork. But doctors often have to do administrative tasks like keeping records, making sure rules are followed, and dealing with insurance, which makes their daily work load even heavier. These extra layers can make it harder to spend time with patients in a meaningful way.